Spatial–temporal patterns in anthropogenic and biomass burning emission contributions to air pollution and mortality burden changes in India from 1995 to 2014 - B. Luo; Y. Zhang; T. Tang; T. Tang; H. Zhang; J. Hu; J. Mu; W. Wang; L. Xue (Atmospheric Chemistry and Physics)
Anthropogenic (ANTHRO) and biomass burning (BB) emissions are major contributors to ambient air pollution, with the latter playing a particularly dominant role in nonurban regions. India has experienced a dramatic deterioration in air quality over the past few decades, but no systematic assessment has been conducted to investigate the individual contributions of ANTHRO and BB emission changes over the long term in India, particularly in nonurban areas. In this study, we conduct a comprehensive analysis of the long-term trends in particulate matter with aerodynamic diameters < 2.5 µm (PM2.5) and ozone (O3) in India and their mortality burden changes from 1995 to 2014, using a state-of-the-art high-resolution global chemical transport model (CAM-chem). Our simulations reveal a substantial nationwide increase in annual mean PM2.5 (6.71 µg m−3 per decade) and O3 (7.08 ppbv per decade), with the Indo-Gangetic Plain (IGP) and eastern central India serving as hotspots for PM2.5 and O3 trend changes, respectively. It is noteworthy that substantial O3 decreases were observed in the northern IGP, potentially linked to nitric oxide (NO) titration due to a surge in nitrogen oxides (NOx) emissions. Sensitivity analyses highlight ANTHRO emissions as primary contributors to rising PM2.5 and O3, while BB emissions play a prominent role in winter and spring. In years with high BB activity, the contributions from BB emissions to both PM2.5 and O3 changes were comparable to or even exceeded ANTHRO emissions in specific areas. We further estimate that the elevated air pollutant levels were associated with increased premature mortality attributable to PM2.5 and O3, leading to 97 830 and 73 911 deaths per decade. Although there has been a decrease in premature mortality per capita in the IGP region, population increase has offset its effectiveness.